Encapsulation of folic acid in different silica porous supports: A comparative study. (1st April 2016) - Pérez-Esteve, Édgar; Ruiz-Rico, María; de la Torre, Cristina; Villaescusa, Luis A.; Sancenón, Felix; Marcos, María D.; Amorós, Pedro; Martínez-Máñez, Ramón; Barat, José Manuel
Highlights: Gated supports able to modulate the release of folic (FA) acid were developed. FA loading optimization allowed obtaining efficient smart delivery systems (SDS). Developed SDS control FA release exposition through the gastrointestinal tract. Supports pore system was correlated to loading efficiency and release kinetics. Developed supports lead to good cytocompatibility. Abstract: Although folic acid is essential to numerous bodily functions, recent research indicates that a massive exposition to the vitamin could be a double-edged sword. In this study, the capacity of different caped mesoporous silica particles (i.e. Hollow Silica Shells, MCM-41, SBA-15 and UVM-7) to dose FA during its passage through the gastrointestinal tract has been evaluated. Results confirmed that the four capped materials were capable to hinder the delivery of FA at low pH (i.e. stomach) as well as able to deliver great amounts of the vitamin at neutral pH (i.e. intestine). Nevertheless, the encapsulation efficiency and the deliver kinetics differed among supports. While supports with large pore entrance exhibited an initial fast release, MCM-41, showed a sustained release along the time. This correlation between textural properties and release kinetics for each of the supports reveals the importance of a proper support selection as a strategy to control the delivery of active molecules.